DOKTRIN MANUSIA DAN DOSA - Verra Verra; Rafiela Loli; Tita Tita (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the doctrine of humanity and sin from a theological perspective, particularly in the context of the redemptive work of Jesus Christ. Humans were created by God in His image and likeness, with the purpose of living in a loving relationship and obedience to Him. However, humans fell into sin, which led to total corruption in various aspects, such as spiritual, moral, and social. As a result, humans are unable to save themselves, and only through God's grace can humans be freed. This study uses a literature study method to analyze the views of theologians such as Augustine, Louis Berkhof, Stephen Tong, and John Calvin, as well as relevant academic sources. The results show that sin is not merely an act of breaking rules, but an existential condition that separates humans from God. The redemption accomplished by Jesus Christ through His death on the cross is the only way to restoration and forgiveness for humans. Correctly understanding the doctrine of humanity and sin helps believers live in an attitude of repentance, receive grace, and carry out ethical responsibilities amidst a world full of sin and moral crisis. Thus, this doctrine becomes the basis for the formation of true Christian character and encourages believers to bring God's love and justice into their daily lives.